2006
DOI: 10.1111/j.1551-2916.2006.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersing Multi-Component and Unstable Powders in Aqueous Media Using Comb-Type Anionic Polymers*

Abstract: We have investigated the effect of polymeric dispersants on the rheological properties and consolidation behavior of concentrated cemented carbide (WC-Co) and magnesia (MgO) suspensions. The relatively novel types of comb-type anionic polymers with grafted non-ionic side chains are effective dispersants also in multi-component powder mixtures with a complex solution and surface chemistry and result in more robust suspensions at significantly higher solids loading compared with e.g., a traditional cationic poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…These side chains, which are less sensitive to ionic strength, will provide a short-range repulsive steric barrier that is able to counter van der Waals forces when the double layer is highly compressed. Direct evidence of the steric contribution of the PEO segment in comb-like acrylic acid backbone grafted with PEO chains has been produced by Palmqvist et al [20] and by Laarz et al [19] by means of AFM measurement. Given the fact that the DLS technique provides dimensions corresponding to an equivalent sphere size including both the electrostatic double layer and the adsorbed polymer, a rough estimation of the thickness of the adsorbed layer in the case of AMPS-MPEG copolymer may be obtained by subtracting the equivalent sphere hydrodynamic radius from that obtained with AMPS-100, which is known to adopt a flat conformation on alumina particles.…”
Section: Copolymer Dispersal Effectmentioning
confidence: 97%
See 2 more Smart Citations
“…These side chains, which are less sensitive to ionic strength, will provide a short-range repulsive steric barrier that is able to counter van der Waals forces when the double layer is highly compressed. Direct evidence of the steric contribution of the PEO segment in comb-like acrylic acid backbone grafted with PEO chains has been produced by Palmqvist et al [20] and by Laarz et al [19] by means of AFM measurement. Given the fact that the DLS technique provides dimensions corresponding to an equivalent sphere size including both the electrostatic double layer and the adsorbed polymer, a rough estimation of the thickness of the adsorbed layer in the case of AMPS-MPEG copolymer may be obtained by subtracting the equivalent sphere hydrodynamic radius from that obtained with AMPS-100, which is known to adopt a flat conformation on alumina particles.…”
Section: Copolymer Dispersal Effectmentioning
confidence: 97%
“…They showed that above pH 6, acrylic acid groups ensure a strong anchoring effect on oppositely charged oxide surfaces, whereby the neutral PEO teeth extend away from the particle surface and regulate the adsorbed layer density and thickness. More recently, Laarz et al [19] investigated the effect of comb-like polymeric dispersants on the rheological properties and consolidation behavior of concentrated cemented carbide (WC-Co) and magnesia (MgO) suspensions. They showed the possibility of tailoring the repulsive range of the comb-type copolymers by controlling the molecular weight of the grafted PEO-side chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the slope of the fluidity/adsorption relationship, results from a combination between backbone charge density and the adsorbed layer thickness. The increase of the side chain density or length leads to thicken or densify the adsorbed layer rising the repulsive steric forces as shown by AFM studies [11,12] or theoretical calculations [13]. Theoretical models which are validated by experimental data can help to tackle the rheology of cement paste such as the conformation model for PCE [12] or the model for predicting the yield stress of a suspension called Yodel [14,15].…”
Section: Introductionmentioning
confidence: 97%
“…Besides, the volume of the final sediment layer was less than that of the BT 4 suspension without the presence of any polymer, as an indication of denser packing of particles. 21,27 If more than 0.5 wt % PAC1 was added, the resulting suspensions became more stabilized and remained cloudy even settled after 30 days. Similar sedimentation behaviors were observed for the BT 4 suspensions with other three PACs, as are shown in Figures 3-5.…”
Section: Suspensionsmentioning
confidence: 98%